2017
DOI: 10.1016/j.purol.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome de la maladie post-orgasmique

Abstract: Le "postorgasmic illness syndrome" (POIS) ou « syndrome de la maladie post-orgasmique » (SMPO) est un syndrome rare décrit récemment qui regroupe un ensemble de symptômes cliniquesphysiques ou cognitifs-apparaissant électivement après une éjaculation ou un orgasme et pouvant perdurer plusieurs jours. Les étiologies et les mécanismes physiopathologiques du POIS restent discutés. Une allergie à une des protéines composant le liquide séminal ou à une protéine excrétée pendant l'éjaculation, une origine psychosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Using data from 57 reported cases of men with POIS, from which Waldinger et al published 47 [1, 2], we found that the presentation of POIS was highly variable: concentration difficulties, extreme fatigue, exhaustion and fever, body warmth, perspiration, shivering, mood disturbances, irritability and memory difficulties [18]. This is why we think that the discoverers of this syndrome, after further research, suggested 5 preliminary diagnostic criteria to assess the large spectrum of this disease [2].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using data from 57 reported cases of men with POIS, from which Waldinger et al published 47 [1, 2], we found that the presentation of POIS was highly variable: concentration difficulties, extreme fatigue, exhaustion and fever, body warmth, perspiration, shivering, mood disturbances, irritability and memory difficulties [18]. This is why we think that the discoverers of this syndrome, after further research, suggested 5 preliminary diagnostic criteria to assess the large spectrum of this disease [2].…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of POIS is not clear yet and it has been explored by few studies so far; hypotheses include: an immunological phenomenon [25], an opioid-like withdrawal [6], a neuroendocrine response [7], a transient deregulation of the autonomic nervous system [8], a hypersensitivity and disordered cytokines [10, 11].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations